Systematic Literature Review (SLR) : Dampak Financial Technology dan Literasi Keuangan pada Kinerja Keuangan Usaha Mikro Kecil Menengah di Kalimantan Timur - Muhammad Astri Yulidar Abbas; Hutauruk, Martinus Robert; Sri Wahyuti; Siti Maulina; Putri Indardaini (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the impact of the use of financial technology (fintech) and financial literacy on the financial performance of micro, small, and medium enterprises (MSMEs) in East Kalimantan. Micro, Small, and Medium Enterprises (MSMEs) in East Kalimantan have an important role in supporting the regional economy, especially in supporting the acceleration of the development of the Indonesian Capital City (IKN). However, MSMEs face various challenges in improving their efficiency and financial performance. Empirically, research shows that MSMEs that adopt fintech experience increased access to financing and efficiency of financial transactions. Using the Systematic Literature Review (SLR) approach, this study integrates findings from various relevant previous studies to identify the relationship between fintech, financial literacy, and MSME performance. Fintech has been shown to provide wider and more efficient access to financing, while financial literacy allows MSMEs to manage their finances better. This study also explores secondary data on the level of fintech adoption and financial literacy in East Kalimantan to provide in-depth local context. The results of the study are expected to contribute to the development of policies that support the digital transformation of MSMEs and increase the competitiveness of the local economy in the digital era.